Identification and analysis of BAHD superfamily related to malonyl ginsenoside biosynthesis in Panax ginseng - Ping Wang; Yan Yan; Min Yan; Xiangmin Piao; Yingping Wang; Xiujuan Lei; He Yang; Nanqi Zhang; Wanying Li; Peng Di; Limin Yang (Frontiers in Plant Science, 2023)
IntroductionThe BAHD (benzylalcohol O-acetyl transferase, anthocyanin O-hydroxycinnamoyl transferase, N-hydroxycinnamoyl anthranilate benzoyl transferase and deacetylvindoline 4-O-acetyltransferase), has various biological functions in plants, including catalyzing the biosynthesis of terpenes, phenolics and esters, participating in plant stress response, affecting cell stability, and regulating fruit quality. MethodsBioinformatics methods, real-time fluorescence quantitative PCR technology, and ultra-high-performance liquid chromatography combined with an Orbitrap mass spectrometer were used to explore the relationship between the BAHD gene family and malonyl ginsenosides in Panax ginseng. ResultsIn this study, 103 BAHD genes were identified in P. ginseng, mainly distributed in three major clades. Most PgBAHDs contain cis-acting elements associated with abiotic stress response and plant hormone response. Among the 103 genes, 68 PgBAHDs are WGD (whole-genome duplication) genes. The significance of malonylation in biosynthesis has garnered considerable attention in the study of malonyltransferases. The phylogenetic tree results showed 34 PgBAHDs were clustered with genes that have malonyl characterization. Among them, seven PgBAHDs (PgBAHD4, 45, 65, 74, 90, 97, and 99) showed correlations > 0.9 with crucial enzyme genes involved in ginsenoside biosynthesis and > 0.8 with malonyl ginsenosides. These seven genes were considered potential candidates involved in the biosynthesis of malonyl ginsenosides. DiscussionThese results help elucidate the structure, evolution, and functions of the P. ginseng BAHD gene family, and establish the foundation for further research on the mechanism of BAHD genes in ginsenoside biosynthesis.